Analysis of the degradation of encapsulant materials used in photovoltaic modules exposed to different climates in China. (December 2019) - Han, Huili; Yan, Huan; Wang, Xuemeng; Zhang, Kai; Huang, Jiapei; Sun, Yunlin; Liu, Jiangfeng; Verlinden, Pierre J.; Altermatt, Pietro; Liang, Zongcun; Shen, Hui
Highlights: The EVA samples used in this study are divided into four typical categories according to the different micro-environmental conditions within the modules: namely to compare samples either at the front or at the back the cells and samples located either at the center of a cell or between cells or at the edge of a cell. The optical characterization shows that the transmittance of EVA samples on the front and at the center of a cell is lower than EVA samples around the edge of the module and between cells. The FTIR analysis of the chemical structure revealed that the EVA samples from the edge to the center of cells showed an increase in the absorbance bands caused by photo-thermal degradation products. Because moisture and oxygen diffuse through the backsheet and from the edge of the module, and also around the cells toward the front-center of the cells, the degree of deacetylation process of the EVA samples from SM55 modules, submitted to a hot-humid climate, is lower than that of the EVA samples from M75 modules, submitted to a hot-dry climate with higher solar irradiation. Thermograms indicated that there is a two-step thermal degradation process: the deacetylation process in the vinyl acetate fraction, and the second stage is the complete chain scission of the residual main chain. The relative crystallinity of EVA sample from area D to A not only for SM55 module but also for M75 module is increased, which can be confirmed by the results of the X-ray diffraction. The results showed that there is a strong influence of environmental stresses on the aging behavior of polymeric encapsulant materials. Not only the degradation behaviors of encapsulant materials from different modules exposed in different climates are different, but also the encapsulant materials from different areas of one module. Abstract: This work investigates the degradation mechanisms of polymeric encapsulants used in photovoltaic modules. Two groups of photovoltaic modules, which were exposed to two typical climates, namely a hot-humid climate and a hot-dry climate, were investigated. Both types of modules were produced by Siemens Solar in 1992 and exposed to outdoor sunlight and the climate for 18 years. The results show that, depending on the climate conditions, the polymeric encapsulant materials exhibit different degradation mechanisms regarding the optical, chemical and morphological properties. The aging of polymeric encapsulant materials is, on the one hand, related to the working environment (moisture, sunlight intensity, UV content and temperature) and, on the other hand, also the conditions are not uniform across the modules: moisture ingress is more important at the edge of the module, oxygen diffusion is more important between cells than at the center of a cell, the module temperature is not uniform.